Diferentes frequências de alimentação na terminação de cordeiros utilizando resíduo úmido de cervejaria - Gallarreta, Bernardo da Trindade (2024)
The objective was to evaluate the consumption, performance, ingestive behavior and characteristics of the carcass and non-carcass components of lambs finished in confinement receiving wet brewery residue as a source of roughage subject to different feeding frequencies. 30 uncastrated male lambs were used, coming from a cross between the Texel and Ile de France breeds. At the beginning of the experiment, the animals had an average age of 72.7±6 days and an average weight of 25.44±4.1 kg. The treatments consisted of three different feeding frequencies: once a day (08:00), twice a day (08:00 and 18:00) and three times a day (08:00, 13:00). 00 and 18:00 hours). The roughage:concentrate ratio used was 46.9:53.1 based on dry matter. There was an effect of feeding frequency on the consumption of CP, EE, NDF and ADF in kg/day, NDF and ADF in % of BW and EE, NDF and ADF in g/kg BW0.75, as well as for the variables weight and proportion of ribs, weight and proportion of kidneys and weight of rumen plus reticulum (Rum+Ret). As for the other variables evaluated, there was no effect of feeding frequency remaining similar (P>0.05) between treatments. Under the conditions of this work, based on the results, it is concluded that a daily diet is recommended for finishing lambs in confinement.